Sustainable Consumption Communities – Relevance and Acceptance - Andreas Mann; Sven Kilian (Marketing Review St.Gallen, 2023)
Sustainable consumption communities are voluntary associations of private individuals who aim to contribute to the sustainable transformation of the society and the economy. In this paper, the public acceptance of such communities as well as corresponding determinants and barriers are empirically analysed and recommendations for action are derived.
Keywords: 650